Real talk about classroom management : 50 best practices that work and show you believe in your students - Pariser, Serena (Thousand Oaks : Corwin, 2018)
Learn From a teacher who's been through it all! Real talk about thriving and learning in the classroom When most educators think of K-12 classroom management, we traditionally focus on ways to keep students quiet, well behaved, and on task. In order to better prepare them for the realities of today's world, we should instead think of classroom management as preparing students to work collaboratively, form their own thoughts and opinions, stay independently motivated, and listen to their classmates. In the interconnected 21st century, classroom management is about building students up, not breaking them down. With those changes in mind, this handy guide offers 50 proven best practices for managing today's classroom in a user-friendly format, complete with just-in-time tools and relatable teacher-to-teacher anecdotes and advice. Culled from years of real-world classroom experience, this book will give you the tips and tricks you need to succeed all school year long, including Making the pivotal first weeks of school count Forming positive relationships with your students Inspiring creativity and maintaining discipline through curriculum and instruction Utilizing other adults (parents, teachers, and administrators) as resources Wowing your students with'spins' and making a lasting emotional impact Keeping yourself sane, from maintaining work-life balance to managing professional relationships This book delivers the mission-critical information every teacher needs to effectively manage the classroom, and prepare students with the social skills and communication tools they'll need to succeed in today's world.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Classroom management